Design and performance analysis of high-altitude UAVs: trends, challenges, and innovations - Shubham Rai; Abhishek Rawat; Ajit Kumar (Discover Applied Sciences)
Abstract High-altitude unmanned aerial vehicles (UAVs) operate in extreme environmental conditions that impose significant constraints on design, stability, and performance. This paper presents a structured review of the major challenges associated with the development of fixed-wing, multirotor, and hybrid Vertical take-off Landing (VTOL) UAVs, with emphasis on their suitability for high-altitude, long-endurance missions. UAVs are classified based on design, weight, aerodynamics, and operational role to provide clarity in application-specific development. Key design elements such as materials, propulsion systems, airfoils, and structural layout are examined alongside aerodynamic considerations including lift, drag, wing loading, and stability. Special attention is given to VTOL systems, focusing on transition dynamics, energy efficiency, and control. The paper also highlights current research gaps, particularly in power systems, thermal regulation, and structural optimization, guiding future innovations in high-altitude UAV technology.